Tingkat Kemampuan Berpikir Kritis Matematika Siswa Sekolah Menengah Kejuruan - Baidowi Baidowi; Ketut Sarjana; Ratih Ayu Apsari; Dwi Novitasari; Ni Made Intan Kertiyani (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
Vocational school students (SMK) are equipped with certain work skills so that later they can enter the labor market immediately after graduating from school. The ability to think critically is one of the skills needed in business and industry. Hence, it needs to be owned by SMK students. This study aimed to determine the level of mathematical critical thinking skills of SMK students. The research was conducted in one of the Vocational Schools in Mataram City. The research sample was 60 students in eleventh grade who were taken using a random sampling technique. The level of mathematical critical thinking skill is obtained through a mathematical critical thinking ability test. Furthermore, interviews were conducted to explore things that were not visible in the students' answers. The results of data processing addressed that the percentage level of mathematical critical thinking skills, namely 0% of students are in the very high level, 15% are in the high level, 25% are in enough level, 42% are in the low level and 18% are in the very low level. This means that more than half of the students have low mathematical critical thinking skills.